There is no God: Psalm 14:1–7 - Uroko, Favour Chukwuemeka (Institut Agama Kristen Negeri Toraja, 2024)
In Nigeria, corruption pervades most sectors, beginning with the executive; the second is the legislature; and the third is the judiciary. The purpose of this article is to examine the aphorism that there is no God in Psalm 14:1–7 and its importance to Nigerians. Several works of literature have not used the aphorism in Psalm 14 in analysing the Nigerian context. Psalm 14 is believed to be written by David, and it shows his cry against corrupters and those who trample upon the rights of the poor in society. This is a qualitative study that used discourse analysis with data gotten from relevant academic literature. Emerged themes include: i) Do as you like (vv. 1); ii) People do not understand (vv. 2–3); iii) the rich and power (vv. 4-6); and iv) judgement is very soon (vv. 5-7). Findings show that in Nigeria, everywhere is pervaded by corruption, beginning with the executive, the legislature, and the judicial arm of government. Most of the policies made by the government are anti-people. Government ministries and parastatals are very much involved in the collection of bribes before doing the right thing.